Are employers offering the right rewards? An investigation into how post-80s and 90s in Shanghai can be attracted, motivated and retained by rewards. - Gao, Ziyan (2013)
This study explores what rewards post-80s and 90s in Shanghai receive and how they think about it. This cohort is worth discovering because their unique context has posed challenges to employers in Shanghai. Qualitative interview is used in this study so that researcher is able to understand why these post-80s and 90s are thinking in this way. By seeing rewards through post-80s and 90s’ perspective, researcher is able to provide legitimate managerial implication for businesses in Shanghai.